Clinical applications of electroconvulsive therapy and transcranial magnetic stimulation for the treatment of major depressive disorder: a critical review. (October 2012) - Baker, Paige L; Trevino, Kenneth; McClintock, Shawn M; Wani, Anna; Husain, Mustafa M
SUMMARY  Depression is a common and debilitating psychiatric disorder that is often unable to be effectively treated with pharmacotherapeutic agents alone. Electroconvulsive therapy (ECT) and transcranial magnetic stimulation (TMS) are among several somatic therapies available for the treatment of major depression. The purpose of this article is to synthesize current information on ECT and repetitive TMS as treatments for pharmacotherapy-resistant major depression regarding its use in neuropsychiatric clinical practice. The current psychiatric literature indicates that both ECT and TMS are effective antidepressant treatments. ECT is a safe and highly effective treatment for depression. The literature also illustrates that TMS has a favorable side-effect profile, excellent tolerability and modest efficacy. To date, additional research is being conducted to further enhance ECT and TMS treatment, and to further define their role in treatment algorithms.